PELATIHAN PENULISAN PROPOSAL SKRIPSI UNTUK MAHASISWA FKIP UNBARA (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Abstract This PKM activity originated from the interest of the lecturers in the Indonesian Language and Literature Education Study Program, Unbara, so that the writing of proposals and reports for lecturers and students in SouthSumatra, OKU Baturaja district, was in accordance with the rules of the Ministry. This form of PKM is a training withthe title